INVENTARIS BERAGAM TANAMAN BERKHASIAT OBAT DI DESA MEKAR JAYA - Medi Andriani; Lia Safitri Nada; Shafira Al Fadhilah; Vira Permata Sari; Nabila Azhari Putri; Anya Aulia Fatihah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Herbal plants have been used by the people of Indonesia since their ancestors passed down from generation to generation to maintain health and treat disease. One of the plants used is the leaves of senduduk and bay leaves. content of secondary metabolites in the leaves of senduduk is flavonoids which are known to reduce cholesterol levels. In bay leaves, chemical compounds in the form of flavonoids and quercetin can lower blood pressure and lower cholesterol levels. The method used is by distributing leaflets, presentation of materials, questions and answers, and the use of herbal plants. From the results of the pre-test and post-test questionnaires from the counseling, it can be concluded that there was an increase in public understanding after the socialization was carried out.